КРИТЕРИЙ УПРАВЛЕНИЯ ЗАДАЧ ОПЕРАТИВНОГО УПРАВЛЕНИЯ ВОДНЫМИ РЕСУРСАМИ ОБЪЕКТОВ ВОДОХОЗЯЙСТВЕННЫХ СИСТЕМ - Кабулов, А.В.; Сейтов, А.Ж.; Кудайбергенов, А.А. (SCIENCE and SOCIETY, 2020)
Improvement of existing and working out the new mathematical models, algorithm and programmed modules of solving the problems of modeling the operational management by the complex of hydrotechnical erections in the water management organization provide inereasing the reliability of timely supply of the required amount of water to consumers.
Keywords: optimal control; methods; channel; water distribution; necessary optimality conditions